LOCAL ECONOMIC STUDY ON TOURISM DEVELOPMENT OF HALAL CASE STUDY: RINJANI CIRCLE AREA, SEMBALUN SUB DISTRICT, EAST LOMBOK DISTRICT - Ima Rahmawati Sushanti; Mustamin H. Idris; Baiq Harly Widayanti (Universitas Muhammadiyah Ponorogo, 2019)
Halal tourism is the brand for West Nusa Tenggara province. Sembalun as one of kosher destination is part of Rinjani circumference and designated as a World Geopark by UNESCO. This study is aimed to assess the local economic empowerment base on halal tourism in Rinjani. The descriptive qualitative method was chosen to analyze the data. TheParticipatory Rural Appraisals used as an instrument to identify the expectations of the local economy, society. The study showed that local economic empowerment that could be developed as follows: 1) Halal food initiative through increasing community participation and skills, involving institutions, providing intensive assistance, and increasing the role of community and institution in creating cooperation, 2) Worship facility, improvement through increasing quality and maintenance of available worship facilities, 3) Services during Ramadan by improving the community and institutional capacity as well as delivering information to tourism operators and visitors, 4) Supporting facilities upgrading through increasing the nullah number of water-friendly toilets both quantity and quality